An efficient algorithm for backbone construction in cognitive radio networks. (3rd February 2020) - Kumar, Santosh; Sharma, Bharti; Singh, Awadhesh Kumar
Summary: Numerous research articles exist for backbone formation in wireless networks; however, they cannot be applied straightforward in cognitive radio network (CRN) due to its peculiar characteristics. Since virtual backbone has many advantages such as reduced routing overhead, dynamic maintenance, and fast convergence speed, we intend to propose a backbone formation protocol in CRN. In this paper, we propose a tree‐based backbone formation protocol along with its maintenance. Our protocol is based on non‐iterative approach, thus leading towards limited message overhead and faster convergence speed. The proposed algorithm first forms the tree by maintaining the parent‐child relationship, and second, the parent nodes are connected together to form the virtual backbone. In the end, we evaluate the performance our protocol through extensive simulations. Abstract : In this article, we propose a non‐iterative protocol for backbone formation in cognitive radio networks. The following flowchart represents an instance of our protocol. In figure 1, we have used three types of messages: build tree message (BTM), acknowledgement (ACK), and negative acknowledgement (NACK).